Buscamos soluciones a conflictos - Tiznado Camacho, Mirtha Elena (2019)
The learning lesson called Looking solutions about conflicts was developed in the social personal area, taking into accent the competence lives and participates democratically in the research for common benefit, the capacity interacts with all the people. The performance was achieved, share activities with them classmates respecting their differences, dealing with kindness and respect, it fulfills its duties in the classroom for the art of all and according to their age._x000D_ In the development of this learning lesson applied motivating activities that promote the achievement of competences, capabilities and performances the pedagogical processes were taken into account as motivation, problematization, learning construction and processing of information, application, transfer and evaluation of learning, further the didactic approaches of social personal area. Problematization information analysis, decision making._x000D_ The active participation of students individual and group was promoted._x000D_ The strategies used were in accordance with the age of the student who are, immerse to the activities of the game and its rules.